2021
DOI: 10.3390/en14185741
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hybrid Hetero-Homo Junction Lead-Free Perovskite Solar Cells by SCAPS Simulator

Abstract: In this work, we report on the effect of substituting the active intrinsic i-layer on a conventional pin structure of lead-free perovskite solar cell (PSC) by a homo p-n junction, keeping the thickness of the active layer constant. It is expected that when the active i-layer is substituted by a p-n homo junction, one can increase the collection efficiency of the photo-generated electrons and holes due to the built-in electric field of the homo junction. The impact of the technological and physical device param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…Decreasing the recombination rate at the CH3NH3PbI3-xCIx/ETL interface is a good way to extract the carriers efficiently. To achieve this condition, the CBO of th CH3NH3PbI3-xCIx layer should be 0-0.3 eV lower than the corresponding band of the ETL The CBO is given by Equation (4) [41].…”
Section: The Initial Psc Vs the Optimized Onementioning
confidence: 99%
See 1 more Smart Citation
“…Decreasing the recombination rate at the CH3NH3PbI3-xCIx/ETL interface is a good way to extract the carriers efficiently. To achieve this condition, the CBO of th CH3NH3PbI3-xCIx layer should be 0-0.3 eV lower than the corresponding band of the ETL The CBO is given by Equation (4) [41].…”
Section: The Initial Psc Vs the Optimized Onementioning
confidence: 99%
“…To achieve this condition, the CBO of the CH 3 NH 3 PbI 3−x CI x layer should be 0-0.3 eV lower than the corresponding band of the ETL. The CBO is given by Equation (4) [41]. CBO = (χ abs − χ ETL )…”
Section: The Initial Psc Vs the Optimized Onementioning
confidence: 99%
“…The analysis of the PCE and the other parameters of the simulated photovoltaic cells the previous studies demonstrated in combination with the results of this research allows to conclude that the model used in this research is reliable. Analyzing works [28][29][30][31], one can draw some conclusions regarding the change in the thickness of the absorber layer, in particular, with an increase in the thickness of the absorber, PCE PSC increases, and one can also notice a tendency towards a decrease in FF. This can be explained by the fact that in the case of an increase in the thickness of the absorbing layer, the Energy.…”
Section: Fig3 Dependence Of the Short-circuit Current And Open-circui...mentioning
confidence: 99%
“…The standard solar spectrum (AM1.5) was used with an incident power density (1000 mW/cm 2 ) at room temperature (300K) and the input parameters of SnO 2 taken from [14,15,20] publication. The perovskite and Spiro-OMeTAD parameters are taken from [2,4,8,18,19] and [4,17,21,[23][24][25][26], respectively. Each layer is given a neutral defect of Gaussian-distribution with energy characteristic of 0.1eVand examined the interface defects layers of (ETM/perovskite) and (perovskite/HTM).…”
Section: Introductionmentioning
confidence: 99%
“…Photovoltaic technology has advanced due to numerous solar device structures and its costeffectiveness and enhanced performance [1,2]. The perovskite absorber-based solar structure has become one of the most emerging PV technologies [3,4]. Perovskite materials exhibit good PV output characteristics due to their high absorption coe cient, adequate bandgap, and lengthy charge-carrier diffusion lengths.…”
Section: Introductionmentioning
confidence: 99%